Evaluation of patients doses at medical imaging departments - Tamam, Nissren; Sulieman, Abdelmoneim; Bradley, D.A. * (Elsevier, 2023)
Radiation exposures for medical purposes is remained the main sources to public from manmade radiation. The aims of the study are to patients’ radiation doses during specific planar radiography procedures. A total of 247 patients were examined at four radiology department in Khartoum state, Sudan. The absorbed dose to air at the center of the beam, including backscattered radiation, is known as the entrance surface air kerma (ESAK, mGy). ESAK (Ke) can be computed using the product backscatter factor (B) and incident air kerma Ki. The mean ESAK(mGy) for the chest, skull, abdomen, hip, lumbar spine and limbs procedures were 0.2, 0.76, 97, 1.88, 1.25, 2.25 and 0.30 mGy, respectively. The average ESAK (mGy) values attained for eight planar radiography procedures are comparable or slightly lesser than the previously published studies for the chest, pelvis, and limbs. The patient doses during the skull, abdomen, hip, and spinal cord (lumbar spine) are lower than the previously published values.